English for T&L - Wan Jumani, Fauzi (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
18 - 20 May 2010. The English for Teaching and Learning (T&L) course for academic staff had participants walking in the class voluntarily rather than being skeptical about participating in the course. All participants representing their groups modeled their ‘masks’ which were symbolic of themselves.